Pengukuran Quality of Life Menggunakan Kuesioner SF-36 pada Pasien Hipertensi - Fahamsya, Arifina; Listina, Osie; Maulinda, Yanda Rizqi (Biocity Journal of Pharmacy Bioscience and Clinical Community, 2025)
A rise in arterial blood pressure of 140/90 mmHg or higher is referred to as hypertension. One statistic used to assess how well health services are being prevented and treated is quality of life. Determining the characteristics of hypertension patients at the Talang Community Health Center, assessing their quality of life there, and identifying the factors affecting their quality of life were the goals of this study. This kind of study was quantitative, descriptive, and employed a cross-sectional technique. There were eighty responders in the study sample. Non-probability sampling using a successive sampling method was the sampling strategy used. The findings of the bivariate analysis indicated that the physical component summary was significantly correlated with age, gender, and duration of suffering, whereas the mental component summary was correlated with education and duration of suffering (p <0.05). The multivariate analysis's findings indicated that the physical component summary was influenced by age, gender, and length of suffering. On the other hand, the mental component summary was influenced by the length of suffering. Neither the mental nor the physical components were impacted by education. With physical component summary scores of 42.23 and mental component summary scores of 43.10, respondents with hypertension at the Talang Health Center experienced a low quality of life.